ANALISIS SALT CONTENT PADA MEDIA AKAR DAN DAUN MANGROVE SECRETER AVICENNIA Sp. - Yumima Sinyo; Abdulrasyid Tolangara; Ningsi Saibi; Rasmita Hi. Sabtu (EDUKASI, 2022)
The difference in the amount of salt excretion in mangrove species occurs due to differences in Casparian strips (Gasparini strips) in the root endodermis. Mangrove Avicennia sp has salt-secreting glands. These glands secrete NaCl salts through an active process. The purpose of this study was to analyze the salt content in the roots and leaves of the mangrove secreter Avicennia Sp. in Gotowasi Village, East Halmahera. This research was designed based on the type of case study (case study) and quantitative descriptive using a purposive sampling method and research experiments conducted on independent variables. Root samples were taken at the research location, while the salt content measurement was carried out at the UNKHAIR Biology laboratory using a refractometer. Salt content data were analyzed by means of potential water pressure, namely the sum of potential pressure and osmotic pressure. The results showed that the salt content of roots and leaves of Mangrove secreter Avicennia sp in different water conditions. The results of the Salt Content measurement of Avicennia sp roots at high tide conditions at station I, namely 35‰ (per mile), and station II, namely 25‰. Furthermore, the results of the measurement of salt content in water conditions at low tide at station I the average value is 21‰ and station II is 17‰. The measurement results of salt content in Avicennia sp mangrove leaves at high tide conditions at station I is 15‰, while at station II it is 21‰. Furthermore, the results of measuring the salt content in water conditions at low tide at station I, the average value obtained is 25‰. While at station II it is 30‰.